Anti Inflammatory Effect Of Toman Fish (Channa micropeltes) Extract In Wound Healing Process - Maharani Laillyza Apriasari; Dewi Puspitasari; Amy Nindia Carabelly (Berkala Kedokteran, 2018)
Abstract: One phase of wound healing is the inflammatory phase. Haruan fish extract has shown to accelerate the healing process up because it has anti-inflammatory effects. Toman fish originates from the same genus as the Haruan fish, but its anti-inflammatory effect remains unknown. It was done to analyzed anti-inflammatory effects of Toman fish extract. This study was true experimental design with posttest-only control design. Twenty-seven male mice of Balb-C strain were divided into 3 groups. Incision wound of 1 cm was made along the back of the mice. Nine mice in each group were sacrificed on 3rd days, then histopathology examination was conducted with Haematoxylin eosin. There were significant differences between treatment group given Toman fish extract and positive control group given Haruan fish extract, and also compared to the negative control group in PMN cell examination. There were significant differences between treatment group given Toman fish extract and positive control group given Haruan fish extract compared to negative controls on the number of macrophage cells. Toman fish extract could lower the number of PMN cells and was able to increase the number of macrophages on the 3rd days. Toman fish has anti-inflammatory effects on the wound healing process. Keywords: Anti-inflammatory effects, haruan fish extract, macrophages, PMN cells, toman fish extract